Hardware-Software Co-design for Reconfigurable Field Programmable Gate Arrays Using Mixed-Integer Programming - Ali, F.M.; Al-Hamadi, H.; Ghoniem, A.; Sherali, H.D. (Informatica)
Hardware-Software Co-design for Reconfigurable Field Programmable Gate Arrays Using Mixed-Integer Programming